Sistem Pendukung Keputusan Pemilihan Smartphone bagi Content Creator Menggunakan Metode SMART - Budi setio; Muhammad Hadi Wibowo Lubis; Khairul amri marpaung (STKIP Subang, 2026)
The rapid advancement of smartphone technology has provided a wide range of devices with different specifications and prices, making it increasingly difficult for content creators to select a smartphone that best suits their needs. This study aims to develop a Decision Support System (DSS) for smartphone selection using the Simple Multi Attribute Rating Technique (SMART) method. The research employed a quantitative approach by collecting smartphone specification data from official manufacturers and determining evaluation criteria consisting of camera quality, processor performance, RAM capacity, storage capacity, battery capacity, and price. Each criterion was assigned a weight according to its level of importance, followed by normalization, utility value calculation, and ranking using the SMART method. The findings indicate that the SMART method provides an objective and systematic recommendation in determining the most suitable smartphone for content creators. Based on the calculation results, Xiaomi 17 Ultra achieved the highest preference value, followed by Samsung Galaxy S26, Samsung Galaxy S26+, iPhone 15 Pro, and iPhone 16. The proposed decision support system is expected to assist users in selecting smartphones effectively while providing an alternative decision-making model for evaluating technological devices with multiple criteria.